(untitled) (Marketing Journal, 2025)
This article analyzes the theoretical foundations of the market for acceptable agricultural products and the specifics of its development in Uzbekistan. The study presents scientific views on the concept of acceptable agricultural products, the market mechanism, and its institutional framework, based on the GAP (Good Agricultural Practice) and organic standards. It examines the legal framework for the development of the market for acceptable agricultural products in Uzbekistan, analyzes existing opportunities and development directions, and provides scientific and practical conclusions for the development of the industry.